Alendronate Can Improve Bone Alterations in Experimental Diabetes by Preventing Antiosteogenic, Antichondrogenic, and Proadipocytic Effects of AGEs on Bone Marrow Progenitor Cells. (20th October 2016) - Chuguransky, Sara Rocío; Cortizo, Ana María; McCarthy, Antonio Desmond
Abstract : Bisphosphonates such as alendronate are antiosteoporotic drugs that inhibit the activity of bone-resorbing osteoclasts and secondarily promote osteoblastic function. Diabetes increases bone-matrix-associated advanced glycation end products (AGEs) that impair bone marrow progenitor cell (BMPC) osteogenic potential and decrease bone quality. Here we investigated the in vitro effect of alendronate and/or AGEs on the osteoblastogenic, adipogenic, and chondrogenic potential of BMPC isolated from nondiabetic untreated rats. We also evaluated the in vivo effect of alendronate (administered orally to rats with insulin-deficient Diabetes) on long-bone microarchitecture and BMPC multilineage potential. In vitro, the osteogenesis (Runx2, alkaline phosphatase, type 1 collagen, and mineralization) and chondrogenesis (glycosaminoglycan production) of BMPC were both decreased by AGEs, while coincubation with alendronate prevented these effects. The adipogenesis of BMPC (PPAR γ, intracellular triglycerides, and lipase) was increased by AGEs, and this was prevented by coincubation with alendronate. In vivo, experimental Diabetes (a) decreased femoral trabecular bone area, osteocyte density, and osteoclastic TRAP activity; (b) increased bone marrow adiposity; and (c) deregulated BMPC phenotypic potential (increasing adipogenesis and decreasing osteogenesis and chondrogenesis). Orally administered alendronate prevented all these Diabetes-induced effects on bone. Thus, alendronate could improve bone alterations in diabetic rats by preventing the antiosteogenic, antichondrogenic, and proadipocytic effects of AGEs on BMPC.